“Everything Is Gonna Be Alright with Me”: The Role of Self-Compassion, Affect, and Coping in Negative Emotional Symptoms during Coronavirus Quarantine - Beato, Ana (2022)
Self-compassion has been associated with less distress, particularly when people face stressful and negative events. This study analyzed the mediation role of coping and affect in the relation between self-compassion and negative emotional symptoms during the quarantine decreed by Portuguese Health Authorities in the first phase of the coronavirus outbreak. A total of 428 Portuguese adults (75% women; Mage = 40.8, SD = 11.6) completed an online survey comprised by the Self-Compassion Scale (predictor); Short Version of Depression, Anxiety and Stress Scale (outcomes); The Positive and Negative Affect Schedule; and Brief-COPE. These instruments were adapted to COVID 19’s epidemic. Parallel mediation analyses demonstrated that self-compassionate participants were at less risk of suffering from symptoms of depression, anxiety, and stress during the quarantine. Plus, the relation between self-compassion and depressive, anxious, and stress symptoms were mediated by negative affect and dysfunctional coping style, but only for symptoms of depression. The findings support coping strategies and affect as links between self-compassion and distress but also the importance of separately analyzing the role of self-compassion, negative affect, and coping on symptoms of anxiety, depression, and stress. Low self-compassion might increase negative affect, maintaining stress responses to face demanding events during the COVID-19 epidemic. Results were discussed in the context of the pandemic outbreak.